2021
DOI: 10.3389/fpubh.2021.653612
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Scale-Up Costs of Integrating HIV Self-Testing Into Civil Society Organisation-Led Programmes for Key Populations in Côte d'Ivoire, Senegal, and Mali

Abstract: Despite significant progress on the proportion of individuals who know their HIV status in 2020, Côte d'Ivoire (76%), Senegal (78%), and Mali (48%) remain far below, and key populations (KP) including female sex workers (FSW), men who have sex with men (MSM), and people who use drugs (PWUD) are the most vulnerable groups with a HIV prevalence at 5–30%. HIV self-testing (HIVST), a process where a person collects his/her own specimen, performs a test, and interprets the result, was introduced in 2019 as a new te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
(44 reference statements)
0
8
1
Order By: Relevance
“…To our knowledge, this is the rst published study estimating cost of HIV self-testing in Indonesia or others similar settings in South East Asia, thus we cannot make study comparation to other location in Indonesia or South East Asia. The costs per HIVST kits distributed to client for screening in our study across all area and KPs are higher compare to other similar studies in African countries [15][16][17][18][19] . This nding may due to several factors.…”
Section: Discussioncontrasting
confidence: 52%
“…To our knowledge, this is the rst published study estimating cost of HIV self-testing in Indonesia or others similar settings in South East Asia, thus we cannot make study comparation to other location in Indonesia or South East Asia. The costs per HIVST kits distributed to client for screening in our study across all area and KPs are higher compare to other similar studies in African countries [15][16][17][18][19] . This nding may due to several factors.…”
Section: Discussioncontrasting
confidence: 52%
“…HIVST small-scale health facility distribution channels are part of a national HIVST implementation program with large scale distribution channels for outreach HIVST generating high central costs (16,26), so central costs are likely negligible for these low-scale distribution channels, when run alongside largerscale models. In addition, central costs are also particularly high with the ATLAS integrated approach that entailed a lengthy implementation process with partners (16,17), so even if our cost allocation method of central costs was based on volumes, these central costs would still remain high-as shown by our sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A site is defined either as a primary health care facility for general population and/or key populations, a sexual health clinic, or a community health centre recognized by government authorities. Overall, HIVST kits were distributed by 208 agents (Côte d'Ivoire (16,21). We conducted two economic cost analyses from the provider's perspective: HIVST and HTS.…”
Section: Cost and Programmatic Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This specificity of HIVST kit distribution implies that HIVST beneficiaries (end-users) are not limited to primary contacts. ATLAS's program results have shown that HIVST can reduce stigma; preserve anonymity and confidentiality; reach KPs that do not access testing via other testing approaches; save opportunity costs for users and providers; empower users with autonomy and responsibility; and is noninvasive and easy to use [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%